Pharmacoeconomic analysis of using empegfilgrastim for the treatment of early and locally advanced HER2+ breast cancer in the Russian Federation - M. V. Zhuravleva; K. A. Kokushkin; E. A. Luchinin; E. V. Luchinina; T. R. Kameneva; E. V. Kuznetsova; V. S. Krysanova; E. V. Makarova; L. G. Zhukova (IRBIS LLC, 2024)
Objective: to assess budget impact of using empegfilgrastim for the prevention of febrile neutropenia in patients with early and locally advanced human epidermal growth factor receptor 2 positive (HER2+) breast cancer who receive neoadjuvant "docetaxel / carboplatin / trastuzumab + pertuzumab" regimen, considering possible subsequent adjuvant therapy with trastuzumab emtansine or trastuzumab within the Russian healthcare system.Material and methods. We searched and analyzed published clinical, epidemiological and pharmacoeconomic studies as well as regulatory and legal documents. A decision tree model was constructed to reflect the probabilities of switching to different adjuvant therapy regimens depending on the achievement of pathomorphological complete response in patients with early and locally advanced HER2+ breast cancer. The budget impact analysis was carried out comparing two primary prophylactic options, empegfilgrastim and filgrastim.Results. Despite the higher costs of prevention with empegfilgrastim compared to filgrastim (249 vs. 134 thousand rubles), due to the higher rate of achieving a pathomorphological complete response and, accordingly, fewer cases requiring adjuvant therapy with the more expensive trastuzumab emtanzine, savings of 916 thousand rubles per 1 patient per 1 year of therapy are possible. In general, prophylaxis in the target population diagnosed with early and locally advanced HER2+ breast cancer using empegfilgrastim will result in a cost reduction of 9.4 billion rubles per 1 year compared to filgrastim.Conclusion. Empegfilgrastim prophylaxis, despite its higher annual cost, is an efficient option within the Russian healthcare system. In addition to reducing the incidence of febrile neutropenia, the frequency and dose of chemotherapy are preserved, resulting in increased efficacy of the primary therapy.